Kedudukan Hukum Perkawinan yang Tidak Direstui Orang Tua dengan Alasan Tidak Dilakukannya Khitbah Menurut Hukum Islam Dikaitkan dengan Instruksi Presiden Nomor 1 Tahun 1991 tentang Kompilasi Hukum Islam - Indira Ramadhani Lisyanto; Renny Supriyatni; Djanuardi Djanuardi (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
Marriage is sacred, involving various things, namely the parties concerned, religion and beliefs, even relating to living law and national law. Based on Islamic law, the legal requirements of marriage, namely the pillars of marriage, must be fulfilled. One aspect of the pillars of marriage is that there must have a marriage guardian, but there are parents who are not willing to become marriage guardians because khitbah is not carried out. This study aims to examine how the legal position of marriage that is not approved by parents because khitbah is not carried out. This research method is normative legal research, where secondary data is used, namely legal materials in the form of related laws and regulations, as well as Islamic law. As a result, khitbah is not an aspect that determines whether a marriage is valid or not. Marriage is considered valid if the prospective bride and groom follow the provisions of the pillars of marriage.